PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MENGGUNAKAN PENDEKATAN REALISTIKC MATHEMATIC EDUCATION MADRASAH IBTIDAIYAH KABUPATEN MERANGIN - Hasmawati (Pendidikan Matematika | STKIP YM Bangko, 2022)
This research started from the low mathematical ability of students, namely the ability to understand mathematical concepts. This can be seen in the daily scores of the fifth grade students of MIS Nurul Ijitihad, Lubuk Gaung Village, Merangin Regency which is under the Minimum Completeness Criteria (KKM), so that mathematics learning has not been running as expected. This study aims to describe the process of improving students' mathematical concept understanding skills through the Realistic Mathematical Education approach to fifth grade students of Madrasah Nurul Ijtihad Swasta, Lubuk Gaung Village, Kab. Merangin. The research subjects were students of Madrasah Nurul Ijtihad Private, Lubuk Gaung Village, Kab. Merangin which amounted to 19 people. The type of research used is classroom action research. This research uses a qualitative approach which is supported by a quantitative approach. Qualitative data obtained through observation of student activities.Quantitative data was obtained through a test of the ability to understand mathematical concepts which was carried out at the end of each lesson in cycle I and cycle II. Quantitative data analysis technique with percentage formula. The data obtained are presented in tabular form. The results show that the Realistic Mathematical Education approach can improve the ability to understand mathematical concepts of fifth grade students of Madrasah Nurul Ijtihad Swasta, Lubuk Gaung Village, Kab. Merangin. This increase can be seen from the average test results of students' mathematical concept understanding ability in cycle I and cycle II. In the first cycle, the average value of the students' mathematical concept understanding ability test was 69.16 in the sufficient category. In the second cycle the average test score of 82.63 students was categorized as very good. The percentage increase in the average score of students from the first cycle is 13.47%